Matrix Metalloproteinase-2 (MMP-2): As an Essential Factor in Cancer Progression - Reddy, Ramakkamma Aishwarya; Varshini, Magham Sai; Kumar, Raman Suresh (Recent Patents on Anti-Cancer Drug Discovery, 2025)
The development of cancer has been a multistep process involving mutation, proliferation, survival, invasion, and metastasis. Of all the characteristics of cancer, metastasis is believed to be the hallmark as it is responsible for the highest number of cancer-related deaths. In connection with this, Matrix metalloproteinases (MMPs), that has a role in metastasis, are one of the novel therapeutic targets. MMPs belong to the family of zinc-dependent endopeptidases and are capable of degrading the components of the extracellular matrix (ECM). The role of MMPs in ECM remodeling includes tissue morphogenesis, uterine cycling, growth, tissue repair, and angiogenesis. During pathological conditions, MMPs play a critical role in the excessive degradation of ECM which includes arthritis, tumour invasion, tumour metastasis, and several other autoimmune disorders. Moreover, they are believed to be involved in many physiological aspects of the cell, such as proliferation, migration, differentiation, angiogenesis, and apoptosis. It is reported that dysregulation of MMP in a variety of cancer subtypes have a dual role in tumour growth and metastasis processes. Further, multiple studies suggest the therapeutic potential of targeting MMP in invading cancer. The expression of MMP-2 correlates with the clinical characteristics of cancer patients, and its expression profile is a new diagnostic and prognostic biomarker for a variety of human diseases. Hence, manipulating the expression or function of MMP-2 may be a potential treatment strategy for different diseases, including cancers. Hence, the present review discusses the therapeutic potential of targeting MMP in various types of cancers and their recent patents.
Keywords: endopeptidases